Nursing of Moruliuschrysophekadion by 4 different Diets - Vannadeth, Phonesay; Chanthakhoun, Vonpasith; Singpa, Bounlam; Tayyamath, Khambou (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The experiments were study on nursing of Morulius Chrysophekadion by 4 different Diets in Thin Chom Statin at Thin Chom Village, Luang PrabangCity, Luang Prabang Province.The aims of this study were comparing the growth of the Morulius Chrysophekadion, the survival rate and the economic income. According to Completed Randomized Design, the CRD were using 4 treatments (3 repetitions per treatment). The diets were as follows: T1= Rice bran 100% , T2= Rice bran 90% + 10% Moinamacrocopa, T3= Rice bran 80% + 20% soybean meal, T4= Rice bran 70% + 30% complete feed. This study was based on stock density of 400 heads/m2 of density, average initial wieght at 0.35 g per fish and long at 3 cm .The cage was design from the nylon net at 1x1x1.5 m of size and deep of the water 1 m. The study was carried out for 45 days. The result was found that the average of fish length significant difference p<0.05 increase highly on T2 = 0.97 cm, T1 = 0.73 cm, T3 = 0.73 cm and T4 = 0.57 cm, respectively. ADG were significant difference p<0.05 increase highly on T2= 0.0089 g, T1= 0.0073 g, T3=0.0071g andT4= 0.0070 g respectively. On another hand, the average survival rate were significant difference p<0.05 increase highly on T3 = 96.83%, T4 = 95.41%, T1 = 92.25% and T2 = 91.58%, respectively. The conversely, income from economic return on total income of each experiment were T1 = 442,800 kip, T2 = 439,600 kip, T3 = 464,800 kip, T4 = 458,000 kip, respectively. The income wereT1=64,534 kip, T2=40,634 kip, T3=83,384 kipT4=25,634 kip respectively.